The Role of Osteoclast Energy Metabolism in the Occurrence and Development of Osteoporosis - Da, Wacili; Tao, Lin; Zhu, Yue (Frontiers in Endocrinology, 2021)
In recent decades, the research on the mechanism of bone metabolic disorders based on energy metabolism has become a craze. Bone resorption of osteoclasts plays an important role in the occurrence and development of osteoporosis. However, the mechanism of osteoclast energy metabolism disorder that interferes with bone homeostasis is still unclear. Bone resorption of osteoclasts is a highly adenosine triphosphate (ATP)-consuming process, which is produced by glycolysis and oxidative phosphorylation. In addition to glucose, fatty acids and amino acids can also be used as substrates to produce energy through oxidative phosphorylation. In this review, we summarize and analyze the energy-based phenotypic changes, epigenetic regulation, and coupling with systemic energy metabolism of osteoclasts during the development and progression of osteoporosis. At the same time, we propose a hypothesis – compensatory recovery mechanism (involving the balance between osteoclast survival and functional activation), which may provide a new idea for the treatment of osteoporosis.